Islamic Nuance in Decorative-Ornament Architecture Art in Nusantara - Abdullah Yusof; Aizan Hj. Ali @ Mat Zin; Ahmad Faisal Abdul Hamid (UIN Sunan Gunung Djati Bandung, 2014)
The advent of Islam in Nusantara sparked new phenomena or changing not only in structure of building construction of religious places, residency and houses but also ornaments and decoration expressing value of beauty of that building. The result of this research tries to reveal how far Islamic influence is working without undermining local aspects of architecture and how Islamic architecture was influenced by other characters in ornament and decorative-ornament artwith various design and sense. Islamic nuances are substantially showed in traditional and contemporary mosque architecture, graveyard, residencies, palaces, historical building and soon and so forth. Although local elementsare clear, and so with Hinduism and Buddhism, animism, colonial influence and other foreign influences including Middle East, Africa, India and China, Islam shows its prominence in interior and exterior ornament as well as its tools.